8-pCPT-conjugated cyclic AMP analogs exert thromboxane receptor antagonistic properties - Sand, Carsten; Grandoch, Maria; Börgermann, Christof; Oude Weernink, Paschal A.; Mahlke, Yvonne; Schwindenhammer, Benjamin; Weber, Artur-Aron; Fischer, Jens W.; Jakobs, Karl H.; Schmidt, Martina (Thrombosis and Haemostasis, 2010)
Membrane-permeable 8-(4-chlorophenylthio)-2'-O-methyl cyclic AMP (8-pCPT-2'-O-Me-cAMP) has been shown to specifically activate cAMP-regulated Epac proteins, without direct effects on protein kinase A and protein kinase G. During isometric tension measurements in thoracic aortic rings from Wistar rats, we observed that 8-pCPT-2'-O-Me-cAMP selectively induced a rightward shift of the concentration response curve for the thromboxane mimetic U46619, without altering the contractile response to noradrenaline. We hypothesised that 8-pCPT-2'-O-Me-cAMP and similar compounds may function as direct thromboxane receptor antagonists. Indeed, in addition to 8-pCPT-2'-OMe-cAMP, also 8-pCPT-cAMP, 8-(4-chlorophenylthio)-adenosine-3',5'-cyclic monophosphorothioate, Rp-isomer (Rp-8-CPT-cAMPS) and 8-CPT-adenosine, but not 8-Bromo-2'-O-Me-cAMP, induced rightward shifts of the contractile response to U46619. Likewise, 8-pCPT-2'-O- Me-cAMP and Rp-8-CPT-cAMPS, but not 8-Bromo-2'-O-Me-cAMP, specifically reduced U46619-induced aggregation of human platelets. In addition, 8-pCPT-2'-O-Me-cAMP and Rp-8-CPT-cAMPS completely reversed U46619-induced reduction of intercellular adhesion molecule-1 expression and migration of human coronary artery endothelial cells. Most important, the cAMP analogs that reduced the contractile response to U46619 also concentration-dependently inhibited binding of the thromboxane receptor radioligand [5,6-3H]SQ29548 to human platelets. We conclude that 8-pCPT-conjugated cAMP analogs exert competitive thromboxane receptor antagonistic properties.
Keywords: Exchange protein directly activated by cyclic AMP; vascular tissue; human platelets; endothelial cells; thromboxane A2